Particulate matter and early childhood body weight. (September 2016) - Kim, Eunjeong; Park, Hyesook; Park, Eun Ae; Hong, Yun-Chul; Ha, Mina; Kim, Hwan-Cheol; Ha, Eun-Hee
Abstract: Concerns over adverse effects of air pollution on children's health have been rapidly rising. However, the effects of air pollution on childhood growth remain to be poorly studied. We investigated the association between prenatal and postnatal exposure to PM10 and children's weight from birth to 60 months of age. This birth cohort study evaluated 1129 mother-child pairs in South Korea. Children's weight was measured at birth and at six, 12, 24, 36, and 60 months. The average levels of children's exposure to particulate matter up to 10 μm in diameter (PM10) were estimated during pregnancy and during the period between each visit until 60 months of age. Exposure to PM10 during pregnancy lowered children's weight at 12 months. PM10 exposure from seven to 12 months negatively affected weight at 12, 36, and 60 months. Repeated measures of PM10 and weight from 12 to 60 months revealed a negative association between postnatal exposure to PM10 and children's weight. Children continuously exposed to a high level of PM10 (> 50 μg/m 3 ) from pregnancy to 24 months of age had weight z -scores of 60 that were 0.44 times lower than in children constantly exposed to a lower level of PM10 (≤ 50 μg/m 3 ) for the same period. Furthermore, growth was more vulnerable to PM10 exposure in children with birth weight < 3.3 kg than in children with birth weight > 3.3 kg. Air pollution may delay growth in early childhood and exposure to air pollution may be more harmful to children when their birth weight is low. Highlights: Effects of particulate matter on children's growth were studied in a birth cohort study in South Korea. Prenatal and postnatal exposure of particulate matter were estimated. Perinatal exposure to particulate matter affects postnatal children's weight. Children's birth weight might impact on the vulnerability to air pollution regarding children's growth.